The Real K-Theory of Compact Lie Groups - Chi-Kwong Fok (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Let G be a compact, connected, and simply-connected Lie group, equipped with a Lie group involution σG and viewed as a G-space with the conjugation action. In this paper, we present a description of the ring structure of the (equivariant) KR-theory of (G,σG) by drawing on previous results on the module structure of the KR-theory and the ring structure of the equivariant K-theory.